The care of Children and Adolescents victims of sexual abuse: An analysis in the Júlio De Castilhos/RS region (Research, Society and Development, 2021)
Children and adolescents are the main victims of violence, because they are in a special condition of development and in most episodes they are victims of violence practiced by relatives or people who should protect them. The nature of the consequences are variable because it will depend very much on the type of care that this victim received and continues to receive throughout life, given that there may be consequences in the short, medium and long term. Thus, this scientific article deals with a verification regarding the application of the protocol provided for in Law 13.431/2017, the Protected Listening Law, in the care of children and adolescents victims of sexual abuse, in the Municipality of Júlio de Castilhos/RS. Regarding the methodology used in the present study, this is a qualitative bibliographical research, since it used doctrines, articles and articles published in newspapers, legal and scientific journals and in virtual environment (internet), as well as field research was carried out, which sought to analyze whether the implementation of a protocol of care for children and adolescents victims of sexual abuse was carried out at the Municipal Office. Thus, the results demonstrate, from the collected data, that there is no legal prediction about this standardization in the Municipality of Júlio de Castilhos, nor does there exist a protocol of attendance with the flows of these services, which means that the attendances are not performed in accordance with the provisions of Law 13.431/2017.